2008
DOI: 10.1002/jbm.b.31132
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of crystalline material in obstructed stents—In need for intra‐luminal surface modification?

Abstract: 75% of the "obstructed" stents showed no significant inner deposits. Obstruction of urine transport and failure of Seldinger technique occurred due to other reasons. Thus, coating of the stent's inner surface may be overrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
4
0
2
Order By: Relevance
“…In experiments with human urine collected from patients, Griffith et al obtained qualitatively similar results to those obtained with the synthetic urine used in this study [8]. In the clinical routine, approximately 10% of all urinary stones were made up of struvite [29] and originated from infection by bacteria that possessed the enzyme urease [15]. Crystallographic analyses showed that often, human "struvite" stones were not monocrystalline, but a mixture of struvite (MgNH 4 PO 4* 6H 2 O) and carbonate apatite (Ca 10 [PO 4 ] 6* CO 3 ) with trace amounts of calcium oxalate [30]; this made exact classification very complicated.…”
Section: Characterization Of Encrustations: Deposits Resemble In Vivosupporting
confidence: 78%
See 1 more Smart Citation
“…In experiments with human urine collected from patients, Griffith et al obtained qualitatively similar results to those obtained with the synthetic urine used in this study [8]. In the clinical routine, approximately 10% of all urinary stones were made up of struvite [29] and originated from infection by bacteria that possessed the enzyme urease [15]. Crystallographic analyses showed that often, human "struvite" stones were not monocrystalline, but a mixture of struvite (MgNH 4 PO 4* 6H 2 O) and carbonate apatite (Ca 10 [PO 4 ] 6* CO 3 ) with trace amounts of calcium oxalate [30]; this made exact classification very complicated.…”
Section: Characterization Of Encrustations: Deposits Resemble In Vivosupporting
confidence: 78%
“…Besides this, there are other factors that account for a change of stents in the daily clinical routine. Laube et al investigated 59 stents that were removed from the patients because of clinically observed "stent obstruction" [15]. This phenomenon is often described by the fact that the urine flow is compromised due to large depositions in the lumen of the stent.…”
Section: Resultsmentioning
confidence: 99%
“…It has to be noted that the novel method does not provide extraction of biofilm deposited on the stent lumen. Laube et al (2008) demonstrated that most (i.e., 75%) of the ureteral stents which seem to be obstructed according to failure of the Seldinger technique (i.e., the failure to introduce a guide wire into the stent lumen), do not show significant intraluminal deposits and, therefore, the biofilm in the inner part of the stent can be regarded as negligible. Furthermore, the luminal biofilm is not in direct contact with the urothelium and rarely responsible for stent dysfunction as the main urine flow occurs outside the ureteral stent ( Yossepowitch et al, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…Beim Einbringen von Kathetern oder Stents in den Harntrakt kann es zu einer potentiellen primären (nosokomialen/ iatrogenen) oder zusätzlichen Keimverschleppung kommen; bei längerer Liegezeit fördern die Fremdmaterialien aufgrund ihrer Oberfläche selbst die StruvitKarbonatapatit-Mineralisation [15,18,21]. Ursache ist die zur Bakterienanhaftung optimal geeignete Oberfläche.…”
Section: Introductionunclassified
“…Unter ungüns-tigen Umständen kann sich in Folge einsetzender intra-und peribakterieller Kristallisationsprozesse und subsequenter Bildung makroskopischer Mikrolithe sehr schnell ein komplikationsreicher "kristalliner Bakterienbiofilm" entwickeln, dessen kristalliner Bestandteil bei Harnleiterschienen von den Mineralen Struvit und Karbonatapatit dominiert wird [18]; Kalziumoxalat und Brushit (Kalziumhydrogenphosphat, CaHPO 4 ) treten nur relativ selten auf (. Abb.…”
Section: Introductionunclassified